Long-Term Evolution of Coal Permeability Under Effective Stresses Gap Between Matrix and Fracture During CO2 Injection - Mingyao Wei; Jishan Liu; Rui Shi; Derek Elsworth; Zhanghao Liu (Transport in Porous Media, 2019)

Effects of Exogenous GA3 and DPC Treatments on Levels of Endogenous Hormone and Expression of Key Gibberellin Biosynthesis Pathway Genes During Stem Elongation in Sugarcane - Li-Hang Qiu; Rong-Fa Chen; Han-Min Luo; Ye-Geng Fan; Xing Huang; Jun-Xian Liu; Fa-Qian Xiong; Hui-Wen Zhou; Chong-Kun Gan; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2019)

Advances in research of the mid-deep South China Sea circulation - Dongxiao Wang; Qiang Wang; Shuqun Cai; Xiaodong Shang; Shiqiu Peng; Yeqiang Shu; Jingen Xiao; Xiaohui Xie; Zhiwei Zhang; Zhiqiang Liu; Jian Lan; Dake Chen; et al. (Science China Earth Sciences, 2019)

The T cell activating properties and antitumour activity of Staphylococcal Enterotoxin-like Q - Yanan He; Yuliang Sun; Yakun Ren; Liang Qiao; Rui Guo; Jiang Du; Xinxing Zhu; Yanli Liu; Juntang Lin (Medical Microbiology and Immunology, 2019)

Excess Copper-Induced Changes in Antioxidative Enzyme Activity, Mineral Nutrient Uptake and Translocation in Sugarcane Seedlings - Qiaoying Zeng; Qiuping Ling; Jiayun Wu; Zhanduan Yang; Rui Liu; Yongwen Qi (Bulletin of Environmental Contamination and Toxicology, 2019)

De novo assembly and transcriptome analysis of differentially expressed genes relevant to variegation in hawthorn flowers - Wei Ji; Wei Zhao; Rong-Chen Liu; Xiao-Bo Jiao; Kai Han; Zhong-Yi Yang; Mei-Ying Gao; Rui Ren; Xiu-Juan Fan; Ming-Xia Yang (Plant Biotechnology Reports, 2019)

A transcriptome analysis uncovers Panax notoginseng resistance to Fusarium solani induced by methyl jasmonate - Diqiu Liu; Qin Zhao; Xiuming Cui; Rui Chen; Xin Li; Bingling Qiu; Feng Ge (Genes & Genomics, 2019)

Thermus caldilimi sp. nov., a thermophilic bacterium isolated from a geothermal area - Meng-Meng Li; Wen-Dong Xian; Xiao-Tong Zhang; Yi-Rui Yin; En-Min Zhou; Yi-Ping Ding; Lan Liu; Bao-Zhu Fang; Wen-Jun Li (Antonie van Leeuwenhoek, 2019)

Pedobacter changchengzhani sp. nov., isolated from soil of Antarctica - Rui-Han He; Zhen-Wei Liu; Yong Yu; Hui-Rong Li; Zong-Jun Du (Antonie van Leeuwenhoek, 2019)

An improved method for detecting BeiDou signal-in-space anomalies from precise ephemerides - Lihong Fan; Rui Tu; Rui Zhang; Zengji Zheng; Xiaochun Lu; Jinhai Liu; Xiaodong Huang; Ju Hong (Acta Geodaetica et Geophysica, 2019)

HprK Xcc is a serine kinase that regulates virulence in the Gram‐negative phytopathogen Xanthomonas campestris - Rui‐Fang Li; Ping Cui; Ping‐Zhen Wei; Xing‐Yan Liu; Ji‐Liang Tang; Guang‐Tao Lu (Environmental Microbiology, 2019)
Summary The HprK serine kinase is a component of the phosphoenolpyruvate phosphotransferase system (PTS) of bacteria that generally regulates catabolite repression through phosphorylation/dephosphorylation of the PTS protein PtsH at a conserved serine residue. However, many bacteria do not encode a complete PTS or even have an HprK homologue. Xanthomonas campestris pv. campestris ( Xcc ) is a pathogen that cause black rot disease in crucifer plants and one of the few Gram‐negative bacteria that encodes a homologue of HprK protein (herein HprK Xcc ). To gain insight into the role of HprK Xcc and other PTS‐related components in Xcc we individually mutated and phenotypically assessed the resulting strains. Deletion of hprK Xcc demonstrated its requirement for virulence and other diverse cellular processes associated including extracellular enzyme activity, extracellular‐polysaccharide production and cell motility. Global transcriptome analyses revealed the HprK Xcc had a broad regulatory role in Xcc . Additionally, through overexpression, double gene deletion and transcriptome analysis we demonstrated that hprK Xcc shares an epistatic relationship with ptsH . Furthermore, we demonstrate that HprK Xcc is a functional serine kinase, which has the ability to phosphorylate PtsH. Taken together, the data illustrates the previously unappreciated global regulatory role of HprK Xcc and previously uncharacterized PTS components that control virulence in this pathogen.

Evaluation of Liquefaction Potential in Saturated Sand under Different Drainage Boundary Conditions—An Energy Approach - Chang-Rui Yao; Bo Wang; Zhi-Qiang Liu; Hao Fan; Fang-Hao Sun; Xin-Hao Chang (Journal of Marine Science and Engineering, 2019)
Drainage conditions are supposed to have significant influence on sand liquefaction behavior. An infiltration device was utilized in cyclic triaxial tests to reproduce different drainage conditions by altering dry density of the within silt. Permeability coefficient ratio (kp) was utilized for quantifying the drainage boundary effect. Cyclic triaxial tests were conducted on saturated Fujian standard sand samples. Test results were used to evaluate the liquefaction potential by using the energy approach. It can be concluded that, if kp increases slightly bigger than zero, excess pore water pressure (EPWP) will respond more fiercely, and the dissipated energy that triggers sand liquefaction will be less. By considering kp, an energy-based database was built by taking kp into consideration and different neural network (NN) models were constructed to predict liquefaction potential by energy approaches accurately under different drainage boundary conditions. It was suggested that the neuro-fuzzy (NF)-based NN model has more satisfactory performance.

Molecular mapping of the gene(s) conferring resistance to Soybean mosaic virus and Bean common mosaic virus in the soybean cultivar Raiden - Mian Wu; Ying-Na Liu; Cong Zhang; Xue-Ting Liu; Cheng-Chen Liu; Rui Guo; Ke-Xin Niu; An-Qi Zhu; Jia-Yin Yang; Jian-Qun Chen; Bin Wang (Theoretical and Applied Genetics, 2019)

Pathogenic mutations in two Chinese patients exhibiting severe early-onset obesity - Yanshan Liu; Wei Yang; Rui Hua; Yingzhi Huang; Xue Zhang (Science China Life Sciences, 2019)

Quality control of marine big data—a case study of real-time observation station data in Qingdao - Chengcheng Qian; Aichao Liu; Rui Huang; Qingrong Liu; Wenkun Xu; Shan Zhong; Le Yu (Journal of Oceanology and Limnology, 2019)

Digestive characteristics and blood chemistry profile of triploid rainbow trout Oncorhynchus mykiss: influence of body size and seasonal variation - Yuqiong Meng; Buying Han; Changzhong Li; Kangkang Qian; Xiaohong Liu; Xuemin Hu; Xu Yang; Haining Tian; Rui Ma (Fisheries Science, 2019)

Wind and sand control by an oasis protective system: a case from the southeastern edge of the Tengger Desert, China - Yun-hu Xie; Xiao-hong Dang; Zhong-ju Meng; Hong-tao Jiang; Xiao-jia Li; Rui-ping Zhou; Dan-dan Zhou; Xiao-xi Liu; Jing Ding; Xue-qin Wu; Yu-hao Wang; Chun-xing Hai; et al. (Journal of Mountain Science, 2019)

Effects of climate change on lake area and vegetation cover over the past 55 years in Northeast Inner Mongolia grassland, China - Yanfei Zhang; Wentao Liang; Zilong Liao; Zhenhua Han; Xiaomin Xu; Rui Jiao; Hualin Liu (Theoretical and Applied Climatology, 2019)

Integrated analysis of miRNAs and their targets reveals that miR319c/TCP2 regulates apical bud burst in tea plant (Camellia sinensis) - Shengrui Liu; Xiaozeng Mi; Ran Zhang; Yanlin An; Qiying Zhou; Tianyuan Yang; Xiaobo Xia; Rui Guo; Xuewen Wang; Chaoling Wei (Planta, 2019)

Decreased miR-325-5p Contributes to Visceral Hypersensitivity Through Post-transcriptional Upregulation of CCL2 in Rat Dorsal Root Ganglia - Rui Wu; Ping-An Zhang; Xuelian Liu; Yuan Zhou; Meijie Xu; Xinghong Jiang; Jun Yan; Guang-Yin Xu (Neuroscience Bulletin, 2019)

QTL mapping and genetic effect of chromosome segment substitution lines with excellent fiber quality from Gossypium hirsutum × Gossypium barbadense - Shao-qi Li; Ai-ying Liu; Ling-lei Kong; Ju-wu Gong; Jun-wen Li; Wan-kui Gong; Quan-wei Lu; Peng-tao Li; Qun Ge; Hai-hong Shang; Xiang-hui Xiao; Rui-xian Liu; et al. (Molecular Genetics and Genomics, 2019)

Synthesis and antitumor evaluation of novel fused heterocyclic 1,2,4-triazolo[3,4-b]-1,3,4-thiadiazole derivatives - Xiao-Jia Liu; Hai-Ying Liu; Hai-Xin Wang; Yan-Ping Shi; Rui Tang; Shuai Zhang; Bao-Quan Chen (Medicinal Chemistry Research, 2019)

The faster-onset antidepressant effects of hypidone hydrochloride (YL-0919) - Li-jun Sun; Li-ming Zhang; Dan Liu; Rui Xue; Yan-qin Liu; Lei Li; Ying Guo; Chao Shang; Jun-qi Yao; You-zhi Zhang; Yun-feng Li (Metabolic Brain Disease, 2019)

The effect of interactions between particles on soil infiltrability - Wuquan Ding; Xinmin Liu; Feinan Hu; Hualing Zhu; Yaxue Luo; Song Li; Rui Tian; Bing Bao; Hang Li (Journal of Soils and Sediments, 2019)

Associations of ambient PM2.5 and O3 with cardiovascular mortality: a time-series study in Hefei, China - Han Cheng; Furong Zhu; Ruoqian Lei; Chaowei Shen; Jie Liu; Mei Yang; Rui Ding; Jiyu Cao (International Journal of Biometeorology, 2019)

Effect of genotype and environment on agronomical characters of common vetch (Vicia sativa L.) - Rui Dong; Shu H. Shen; Mohamed Z. Z. Jahufer; De K. Dong; Dong Luo; Qiang Zhou; Xu T. Chai; Kai Luo; Zhi B. Nan; Yan R. Wang; Zhi P. Liu (Genetic Resources and Crop Evolution, 2019)

Study on the efficiency of phytoremediation of soils heavily polluted with PAHs in petroleum-contaminated sites by microorganism - Liqun Hou; Rui Liu; Na Li; Yuanyuan Dai; Jun Yan (Environmental Science and Pollution Research, 2019)

Carbon Monoxide Attenuates High Salt-Induced Hypertension While Reducing Pro-inflammatory Cytokines and Oxidative Stress in the Paraventricular Nucleus - Dong-Dong Zhang; Yan-Feng Liang; Jie Qi; Kai B. Kang; Xiao-Jing Yu; Hong-Li Gao; Kai-Li Liu; Yan-Mei Chen; Xiao-Lian Shi; Guo-Rui Xin; Li-Yan Fu; Yu-Ming Kang; et al. (Cardiovascular Toxicology, 2019)

Control and measurement systems for spark ignition rotary engine - Rui Liu; Wanzhong Zhao; Guoan Suo (Energy, Ecology and Environment, 2019)

Analysis and Simulation of the Stratospheric Quasi-zero Wind Layer over Korla, Xinjiang Province, China - Rui Yang; Lingkun Ran; Yuli Zhang; Yi Liu (Advances in Atmospheric Sciences, 2019)

Effects of Exogenous Application of Melatonin on Quality and Sugar Metabolism in ‘Zaosu’ Pear Fruit - Jianlong Liu; Rongrong Yue; Min Si; Meng Wu; Liu Cong; Rui Zhai; Chengquan Yang; Zhigang Wang; Fengwang Ma; Lingfei Xu (Journal of Plant Growth Regulation, 2019)

A new triterpene from the green walnut husks of Juglans mandshurica Maxim - Yuan-Yuan Zhou; Hong-Juan Song; Shuang Guo; Ying Wang; Hui-Rui Gao; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Bing-You Yang; Hai-Xue Kuang (Journal of Natural Medicines, 2019)

Depositional facies and stratal cyclicity of carbonate successions in the Yingshan and Yijianfang Group (Lower-Middle Ordovician) in Yuejin-Tuoputai Region, Tarim Basin, NW China - Cunli Jiao; Zhao Xue-Qin; Rui Zhao; Li Hui-Li; Liu Tian-Jia; Zhao Jia-Hui (Carbonates and Evaporites, 2019)

The origin and distribution of Ordovician Yingshan dolomite on the northern slope of Tazhong area in Tarim Basin - Zhao Jiahui; Zhao Rui; Wu Yasheng; Liu Tianjia; Cui Xuemin; Guo Kunzhang (Carbonates and Evaporites, 2019)

Crystal structure of norsethite-type BaMn(CO3)2 and its pressure-induced transition investigated by Raman spectroscopy - Wen Liang; Lin Li; Yuan Yin; Rui Li; Zeming Li; Xiqiang Liu; Chaoshuai Zhao; Shuguang Yang; Yong Meng; Zengsheng Li; Yu He; Heping Li (Physics and Chemistry of Minerals, 2019)

Metabolomics reveals the drought-tolerance mechanism in wild soybean (Glycine soja) - Xiaoxia Wang; Rui Guo; Mingxia Li; Yuan Liu; Mingli Zhao; Hui Fu; Xueying Liu; Shiyao Wang; Lianxuan Shi (Acta Physiologiae Plantarum, 2019)

Physiological and biochemical responses of Dunaliella salina exposed to acrylamide - Na Ling; Hong-Xiu Li; Hong-Shi Guo; Xiu-Ming Cao; Xiao-Rui Liu (Biologia, 2019)

Aspergilolide, a steroid lactone produced by an endophytic fungus Aspergillus sp . MBL1612 isolated from Paeonia ostii - Pei-Liang Zhang; Gang Wang; Feng-Qing Xu; Jin-Song Liu; Ju-Tao Wang; Rui Zhang; Hai-Tao Liu; Jiang-Miao Hu; Guo-Kai Wang; Pei-Yun Wu (Natural Product Research, 2019)

The spatio-temporal characteristics of drought across Tibet, China: derived from meteorological and agricultural drought indexes - Sisi Li; Zhijun Yao; Zhaofei Liu; Rui Wang; Mingliang Liu; Jennifer C. Adam (Theoretical and Applied Climatology, 2019)

ABA signaling rather than ABA metabolism is involved in trehalose-induced drought tolerance in tomato plants - Wenqing Yu; Ruirui Zhao; Liu Wang; Shujuan Zhang; Rui Li; Jiping Sheng; Lin Shen (Planta, 2019)

Material Flow and Spatial Data Analysis of the Petroleum Use to Carbon Dioxide (CO 2 ) Emissions in Northeast China - Guang‐xin Liu; Ming Wu; Feng‐rui Jia; Qiang Yue; He‐ming Wang (Journal of Industrial Ecology, 2019)
Summary This study investigated the petroleum consumption and petroleum‐related CO 2 emissions (PCOEs) in Northeast China at city level using material flow analysis (MFA) and spatial data analysis (SDA). The petroleum flows for the year 2014 were plotted, and then the spatial patterns, weighted mean centers (WMCs), and spatial autocorrelations of petroleum consumption and PCOEs were calculated, respectively. It was found that Northeast China is a petroleum exploitation‐processing‐export region in China; the total input of petroleum flows comprised two parts—exploitation (about 60%) and import (about 40%). About one third of the total product oil supply flowed into other provinces. In the consumption process, the product oil was dominated by two sectors: the industry sector (45.5%) and the transportation sector (31%). The rate of PCOEs was 36.69 million tonnes in the waste discharge process. Meanwhile, the WMCs of the petroleum consumption and the PCOEs were located in the south of Northeast China. The location of the petroleum pipelines was the factor shown to determine the spatial patterns of petroleum consumption and PCOEs and the hotspots were distributed along the petroleum pipeline, especially in the Circum‐Bohai Sea regions. Economic development in these regions shows a positive dependence on petroleum consumption and generates larger PCOEs. The findings obtained in this study could provide important decision‐making support to low‐carbon development in Northeast China.

Effects of exogenous putrescine on the ultrastructure of and calcium ion flow rate in lettuce leaf epidermal cells under drought stress - Xu Zhu; Lin Wang; Rui Yang; Yingyan Han; Jinghong Hao; Chaojie Liu; Shuangxi Fan (Horticulture, Environment, and Biotechnology, 2019)

Feet-Lock Bolt Application in Cracked Surrounding Rock Tunnels - Xianghui Deng; Daohong Xia; Rui Wang; Yiyuan Liu (Geotechnical and Geological Engineering, 2019)

Modeling the Mechanical Behavior of Gas Hydrate Bearing Sediments Based on Unified Hardening Framework - Kai Li; Rui-ming Liu; Liang Kong; Xin-bo Zhao (Geotechnical and Geological Engineering, 2019)

Comparison of PAH content, potential risk in vegetation, and bare soil near Daqing oil well and evaluating the effects of soil properties on PAHs - Xin Li; Rui Zheng; Qinghua Bu; Qinghai Cai; Yufen Liu; Qian Lu; JiZhe Cui (Environmental Science and Pollution Research, 2019)

Selenium-Yeast Alleviated Inflammatory Damage Caused by Lead via Inhibiting Ras/ERK Pathway and Inflammatory Factors in Chicken Skeletal Muscles - Zhe Liu; Feng Zhang; Ping Lu; Rui Zhao; Hua Zhang; Baifen Song; Liyang Li; Zhijun Wu; Rui Wu (Biological Trace Element Research, 2019)

Dominant Synoptic Patterns and Their Relationships with PM2.5 Pollution in Winter over the Beijing-Tianjin-Hebei and Yangtze River Delta Regions in China - Yuzhi Liu; Bing Wang; Qingzhe Zhu; Run Luo; Chuqiao Wu; Rui Jia (Journal of Meteorological Research, 2019)

Anthropogenic Aerosol Pollution over the Eastern Slope of the Tibetan Plateau - Rui Jia; Min Luo; Yuzhi Liu; Qingzhe Zhu; Shan Hua; Chuqiao Wu; Tianbin Shao (Advances in Atmospheric Sciences, 2019)

Comprehensive assessment of Coupled Model Intercomparison Project Phase 5 global climate models using observed temperature and precipitation over mainland Southeast Asia - Jing Li; Zhaofei Liu; Zhijun Yao; Rui Wang (International Journal of Climatology, 2019)
In this study, the performances of 31 global climate models (GCMs) from Coupled Model Intercomparison Project Phase 5 (CMIP5) were evaluated using observed temperature and precipitation data sets for mainland Southeast Asia (MSA). In addition, the technique for order preference by similarity to ideal solution model (TOPSIS), which is an effective multi‐objective decision method and has been widely applied in systems engineering, was used to comprehensively evaluate the GCMs on a regional scale. The meteorological variables employed included monthly mean, maximum, and minimum air temperature series and annual/seasonal precipitation during the period 1961–2004. Results showed the overall C i values ranged from 0.56 to 0.80. Overall, ACCESS1.0, HadGEM2‐A, HadGEM2‐CC, and CESM1 (BGC) performed better than the other models with respect to air temperature and precipitation over MSA. For meteorological variables, the C i of extreme temperature by GCMs was 0.65 and higher than mean temperature at 0.61. The performance of GCMs in simulating precipitation during wet season was superior to that for annual and dry season precipitation. With respect to evaluation indicators, most of the GCMs assessed in this study failed to capture observed mean annual air temperature and annual precipitation (they underestimated annual air temperature and overestimated mean annual precipitation). When evaluating the performance of the GCMs with respect to reproducing individual climatic variables, the use of various statistical evaluation criteria provided inconsistent results. These results demonstrate the need to consider the influence of different statistical eigenvalues and to employ multiple indicators when possible to enable a comprehensive evaluation of GCMs. The results of this study provide useful information for climate change, water resource, and agricultural management research in MSA.

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Two new sesquiterpenes from cultures of the higher fungus Pholiota nameko - Xiao-Yan Yang; Wan-Rong Niu; Rui-Ting Li; Xiu-Ming Cui; Ji-Kai Liu (Natural Product Research, 2019)

Roseosporol A, the first isolation of a novel sesquiterpenoid from Streptomyces roseosporus - Lina Deng; Rui Wang; Guowei Wang; Mingxu Liu; Zhihua Liao; Guojian Liao; Min Chen (Natural Product Research, 2019)

De novo assembly and discovery of genes involved in the response of Solanum sisymbriifolium to Verticillium dahlia - Liyan Wu; Guanghui Du; Rui Bao; Zhibin Li; Yaju Gong; Feihu Liu (Physiology and Molecular Biology of Plants, 2019)

ANKRD49 inhibits etoposide-induced intrinsic apoptosis of GC-1 cells by modulating NF-κB signaling - Xia Zhou; Wen-tao Wang; Jia Sun; Hong-yan Liu; Xin-yan Bai; Juan-juan Liu; Bao-feng Yu; Rui Guo; Hai-long Wang (Molecular and Cellular Biochemistry, 2019)

Comparison of volatile profiles and bioactive components of sun-dried Pu-erh tea leaves from ancient tea plants on Bulang Mountain measured by GC-MS and HPLC - Wen-jie Zhang; Cong Liu; Rui-juan Yang; Ting-ting Zheng; Miao-miao Zhao; Li Ma; Liang Yan (Journal of Zhejiang University-SCIENCE B, 2019)

Optimizing cold storage of the ectoparasitic mite Pyemotes zhonghuajia (Acari: Pyemotidae), an efficient biological control agent of stem borers - Limin He; Litao Li; Lichen Yu; Xiong Z. He; Rui Jiao; Changxin Xu; Linlin Zhang; Jinli Liu (Experimental and Applied Acarology, 2019)

Salicylic acid involved in chilling-induced accumulation of calycosin-7-O-β-d-glucoside in Astragalus membranaceus adventitious roots - Junpin Liu; Xi Lan; Shuang Lv; Rui Bao; Yuan Yuan; Songquan Wu; Xueli Quan (Acta Physiologiae Plantarum, 2019)

Impact of Seed Coating Agents on Single-Bud Seedcane Germination and Plant Growth in Commercial Sugarcane Cultivation - Yong-Jian Liang; Xiao-Qiu Zhang; Liu Yang; Xi-Hui Liu; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2019)

Hydrogen peroxide and nitric oxide are involved in programmed cell death induced by cryopreservation in Dendrobium protocorm-like bodies - Xue-ru Jiang; Rui-fen Ren; Wei Di; Meng-xue Jia; Ze-di Li; Yan Liu; Rong-fu Gao (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Downregulation of AIF-2 Inhibits Proliferation, Migration, and Invasion of Human Glioma Cells via Mitochondrial Dysfunction - Wei Chen; Hao Liu; Tuo Wang; Gang Bao; Ning Wang; Rui-Chun Li (Journal of Molecular Neuroscience, 2019)

Modeling and performance analysis of precise time transfer based on BDS triple-frequency un-combined observations - Rui Tu; Pengfei Zhang; Rui Zhang; Jinhai Liu; Xiaochun Lu (Journal of Geodesy, 2019)

Effects of periodical drying and non-drying on nutrient content and desiccation tolerance of an intertidal Pyropia yezoensis strain subject to farming conditions - Wen Jun Wang; Xiao Lei Li; Teng Qing Sun; Zhou Rui Liang; Fu Li Liu; Xiu Tao Sun; Fei Jiu Wang (Journal of Applied Phycology, 2019)

Solute Geochemistry and Multivariate Analysis of Water Quality in the Guohua Phosphorite Mine, Guizhou Province, China - Peiyue Li; Rui Tian; Rong Liu (Exposure and Health, 2019)

Impacts of different aged landfill leachate on PVC corrosion - Rui Zhao; Xiaoqian Wang; Xiaolang Chen; Yiyun Liu (Environmental Science and Pollution Research, 2019)

Effects of different substrates on nitrogen and phosphorus removal in horizontal subsurface flow constructed wetlands - Rui Xu; Yong Zhang; Rong Liu; Yun Cao; Guoxiang Wang; Lingchen Ji; Yifan Xu (Environmental Science and Pollution Research, 2019)

The relief effects of organic acids on Scirpus triqueter L. under pyrene–lead stress - Xinying Zhang; Jing Chen; Xiaoyan Liu; Xueping Chen; Lu Liu; Yinghu Niu; Rui Wang (Environmental Science and Pollution Research, 2019)

Reduced hemispheric asymmetry of brain anatomical networks in attention deficit hyperactivity disorder - Dandan Li; Ting Li; Yan Niu; Jie Xiang; Rui Cao; Bo Liu; Hui Zhang; Bin Wang (Brain Imaging and Behavior, 2019)

Decreased cortical and subcortical response to inhibition control after sleep deprivation - Rui Zhao; Xinxin Zhang; Ningbo Fei; Yuanqiang Zhu; Jinbo Sun; Peng Liu; Xuejuan Yang; Wei Qin (Brain Imaging and Behavior, 2019)

A miR-511-binding site SNP in the 3′UTR of IGF-1 gene is associated with proliferation and apoptosis of PK-15 cells - Wenzhen Wei; Gang Wang; Yunyun Cheng; Rui Yang; Jie Song; Shan Huang; Haoyang Li; Hongwei Geng; Hao Yu; Songcai Liu; Linlin Hao (In Vitro Cellular & Developmental Biology - Animal, 2019)

Spatial distribution, source identification, and potential risk assessment of toxic contaminants in surface waters from Yulin, China - Jing Liu; Yongjun Liu; Aining Zhang; Yu Liu; Ying Zhu; Ming Guo; Rui Zhang (Environmental Monitoring and Assessment, 2019)

Salutary effect of fenofibrate on type 1 diabetic retinopathy via inhibiting oxidative stress–mediated Wnt/β-catenin pathway activation - Qiuping Liu; Xian Zhang; Rui Cheng; Jian-xing Ma; Jinglin Yi; Jingming Li (Cell and Tissue Research, 2019)

Theory to describe incomplete ion exchange in charged heterogeneous systems - Wei Du; Xinmin Liu; Rui Li; Rui Tian; Wuquan Ding; Hang Li (Journal of Soils and Sediments, 2019)

Analysis on the Stability of the Inclined Water-Resisting Roof Layer While Mining Under the Confined Aquifer - Yang Hu; Weiqun Liu; Tianran Ma; Rui Yang; Dongxu Liang (Geotechnical and Geological Engineering, 2019)

Impact of the variations in potential glycosylation sites of the hemagglutinin of H9N2 influenza virus - Qianqian Peng; Rui Zhu; Xiaobo Wang; Huoying Shi; Matthew Bellefleur; Shifeng Wang; Xiufan Liu (Virus Genes, 2019)

Intraseasonal Oscillation of Tropospheric Ozone over the Indian Summer Monsoon Region - Yuli Zhang; Chuanxi Liu; Yi Liu; Rui Yang (Advances in Atmospheric Sciences, 2019)

An Innovative Sampling Method for Determining the Scale Effect of Rock Joints - Rui Yong; Ji-Bo Qin; Man Huang; Shi-Gui Du; Jie Liu; Gao-Jian Hu (Rock Mechanics and Rock Engineering, 2019)

Contributions to species of Xylariales in China-1. Durotheca species - Qing De Long; Li Li Liu; Xu Zhang; Ting Chi Wen; Ji Chuan Kang; Kevin David Hyde; Xiang Chun Shen; Qi Rui Li (Mycological Progress, 2019)

Enhanced water solubility, antioxidant activity, and oral absorption of hesperetin by D-α-tocopheryl polyethylene glycol 1000 succinate and phosphatidylcholine - Su-Fang Gu; Li-Ying Wang; Ying-Jie Tian; Zhu-Xian Zhou; Jian-Bin Tang; Xiang-Rui Liu; Hai-Ping Jiang; You-Qing Shen (Journal of Zhejiang University-SCIENCE B, 2019)

Invasive Spartina alterniflora exhibits increased resistance but decreased tolerance to a generalist insect in China - Rui-Ting Ju; Ding Ma; Evan Siemann; Xiang Liu; Ji-Hua Wu; Bo Li (Journal of Pest Science, 2019)

Complete mitochondrial genome of Hemiculter tchangi (Cypriniformes, Cyprinidae) - Yuanchao Zou; Ting Liu; Qian Li; Zhengyong Wen; Chuanjie Qin; Rui Li; Deshou Wang (Conservation Genetics Resources, 2019)

Evaluation of inhaled low-dose formaldehyde-induced DNA adducts and DNA–protein cross-links by liquid chromatography–tandem mass spectrometry - Jiapeng Leng; Chih-Wei Liu; Hadley J. Hartwell; Rui Yu; Yongquan Lai; Wanda M. Bodnar; Kun Lu; James A. Swenberg (Archives of Toxicology, 2019)

Expression and characterisation of a pH and salt tolerant, thermostable and xylose tolerant recombinant GH43 β-xylosidase from Thermobifida halotolerans YIM 90462T for promoting hemicellulose degradation - Yi-Rui Yin; Wen-Dong Xian; Ming-Xian Han; En-Min Zhou; Lan Liu; Dalal Hussien M. Alkhalifah; Wael N. Hozzein; Min Xiao; Wen-Jun Li (Antonie van Leeuwenhoek, 2019)

Transcriptome sequencing to reveal the genetic regulation of leaf margin variation at early stage in birch - Xiuyan Bian; Chang Qu; Manman Zhang; Yidi Li; Rui Han; Jing Jiang; Guifeng Liu (Tree Genetics & Genomes, 2019)

Chromosome level comparative analysis of Brassica genomes - Wenliang Wang; Rui Guan; Xing Liu; Haorui Zhang; Bo Song; Qiwu Xu; Guangyi Fan; Wenbin Chen; Xiaoming Wu; Xin Liu; Jianbo Wang (Plant Molecular Biology, 2019)

Genomic characterization and pathogenicity of porcine deltacoronavirus strain CHN-HG-2017 from China - Meng-Jia Zhang; De-Jian Liu; Xiao-Li Liu; Xing-Yi Ge; Anan Jongkaewwattana; Qi-Gai He; Rui Luo (Archives of Virology, 2019)

Multipotential Toxic Metals Accumulated in Urban Soil and Street Dust from Xining City, NW China: Spatial Occurrences, Sources, and Health Risks - Meng Zhang; Xiaoping Li; Rui Yang; Jiwen Wang; Yuwei Ai; Yu Gao; Yuchao Zhang; Xu Zhang; Xiangyang Yan; Bin Liu; Hongtao Yu (Archives of Environmental Contamination and Toxicology, 2019)

Multi-year assessment of paralytic shellfish toxins in hard clam species along the coastline of Jiangsu Province, China - Xinzhi Wang; Hao Wu; Ying Cheng; Hongmei Wen; Rui Liu; Libao Wang; Chenxiao Shan; Chuan Chai (Acta Oceanologica Sinica, 2019)

Gut microbiota in patients after surgical treatment for colorectal cancer - Ye Jin; Yang Liu; Lei Zhao; Fuya Zhao; Jing Feng; Shengda Li; Huinan Chen; Jiayu Sun; Biqiang Zhu; Rui Geng; Yunwei Wei (Environmental Microbiology, 2019)
Summary Colorectal cancer (CRC) is a common disease worldwide that is strongly associated with the gut microbiota. However, little is known regarding the gut microbiota after surgical treatment. 16S rRNA gene sequencing was used to evaluate differences in gut microbiota among colorectal adenoma patients, CRC patients, CRC postoperative patients and healthy controls by comparing gut microbiota diversity, overall composition and taxonomic signature abundance. The gut microbiota of CRC patients, adenoma patients and healthy controls developed in accordance with the adenoma‐carcinoma sequence, with impressive shifts in the gut microbiota before or during the development of CRC. The gut microbiota of postoperative patients and CRC patients differed significantly. Subdividing CRC postoperative patients according to the presence or absence of newly developed adenoma which based on the colonoscopy findings revealed that the gut microbiota of newly developed adenoma patients differed significantly from that of clean intestine patients and was more similar to the gut microbiota of carcinoma patients than to the gut microbiota of healthy controls. The alterations of the gut microbiota between the two groups of postoperative patients corresponded to CRC prognosis. More importantly, we used the different gut microbiota as biomarkers to distinguish postoperative patients with or without newly developed adenoma, achieving an AUC value of 0.72. These insights on the changes in the gut microbiota of CRC patients after surgical treatment may allow the use of the microbiota as non‐invasive biomarkers for the diagnosis of newly developed adenomas and to help prevent cancer recurrence in postoperative patients.

Two new lignans from Horsfieldia kingii - Bo Liu; Shou-Zhen Du; Fang Kuang; Ying Liu; Xing-Jun Tian; Ye-Gao Chen; Rui Zhan (Natural Product Research, 2019)

Provenance analyses of early Mesozoic sediments in the Ningwu basin: Implications for the tectonic–palaeogeographic evolution of the northcentral North China Craton - Rui Zhou; Dongna Liu; Anchao Zhou; Yu Zou (International Geology Review, 2019)

Whole body vibration with rest days could improve bone quality of distal femoral metaphysis by regulating trabecular arrangement - He Gong; Rui Zhang; Jiazi Gao; Meng Zhang; Bei Liu; Min Zhang; Dong Zhu (Science China Life Sciences, 2019)

Inhibition of YAP with siRNA prevents cartilage degradation and ameliorates osteoarthritis development - Yong Gong; Song-Jian Li; Rui Liu; Jian-Feng Zhan; Chao Tan; Yi-Fei Fang; Yan Chen; Bo Yu (Journal of Molecular Medicine, 2019)

Comprehensive analysis of the whole coding and non-coding RNA transcriptome expression profiles and construction of the circRNA–lncRNA co-regulated ceRNA network in laryngeal squamous cell carcinoma - Rui Zhao; Feng-Qing Li; Lin-Li Tian; De-Si Shang; Yan Guo; Jia-Rui Zhang; Ming Liu (Functional & Integrative Genomics, 2019)

Postprandial change in glucose metabolism at the molecular level in the adipose tissue of omnivorous GIFT Oreochromis niloticus - Jing-Yun Feng; Qin-Qin Liu; Hang-Zhong Xu; Rui-Hong Chen; Li Luo; Shi-Mei Lin; Yong-Jun Chen; De-Shou Wang (Fisheries Science, 2019)

Improved ARAIM fault modes determination scheme based on feedback structure with probability accumulation - Qian Meng; Jianye Liu; Qinghua Zeng; Shaojun Feng; Rui Xu (GPS Solutions, 2019)

Investigation of early Bronze Age civilizations in Yunnan: a scientific analysis of metallurgical relics found at the Guangfentou ruins in Jiangchuan - Guisen Zou; Jianfeng Cui; Xu Liu; Xiaorui Li; Rui Min (Archaeological and Anthropological Sciences, 2019)